Electrocatalytic Behavior of Hydrogenated Pd-Metallic Glass Nanofilms: Butler-Volmer, Tafel, and Impedance Analyses - Sarac; Karazehir, B.; Mühlbacher, T.; Sarac, M.; Eckert, A. (Springer Science and Business Media LLC, 2019)
Electrocatalytic activity and sorption behavior of hydrogen in nanosized Pd–Si–(Cu) metallic glass thin film and Pd thin film electrodes sputtered on a Si/SiO2 substrate were investigated by linear sweep voltammetry, cyclic voltammetry, and electrochemical impedance spectroscopy. The electrode MG4 (Pd69Si18Cu13) exhibits the best performance with the highest electrocatalytic activity in the hydrogen evolution region with less than half of the Tafel slope of Pd thin film of the same thickness and lowest overpotential at 10 mA cm−2. A new approach has been adopted by a nonlinear fitting of the entire region of the polarization curve (far- and near-equilibrium cathodic and anodic regions) to the Butler-Volmer model. α parameter is lowest for the MG2 electrode (Pd79Si16Cu5), marking that nonequilibrium conditions change the reaction kinetics. Together with MG2, MG4 shows the lowest Bode magnitude values for hydrogen sorption and evolution regions, indicating that the bonding and release of hydrogen atoms to the electrode is easier. MG4 electrode shows a dramatic decrease of the overpotential after 100 cycles, yielding an increase in hydrogen activity. Besides, MG4 exhibits the sharpest current density drop in the HER region in cyclic voltammetry compared with other MG and Pd electrodes, indicating higher electrocatalytic activity towards hydrogen evolution. The findings highlight the influence of the selected metallic glasses for the design and development of metal catalysts with higher sorption kinetics and/or electrocatalytic turnover.